Competition and Stability in Indonesian Sharia Banking - Afandi, Johan; Habibah, Muzayyidatul; Fikri, Shofa; Mabruroh, Siti (IAIN Kudus, 2025)
Discussions about the relationship between competition and stability often lead to two opposing views: competition-fragility and competition-stability, which suggest that competition can either weaken or enhance the stability of the banking system. This study examines the impact of competition and efficiency on the stability of Islamic banks in Indonesia during the period 2021 to 2023, focusing on the use of the Herfindahl-Hirschman Index (HHI) and Boone Index as indicators of competition. Bank stability is measured using the Z-score, which reflects financial strength and the risk of bank insolvency.. This study uses HHI as a measure of market concentration and the Boone Index to assess efficiency in the Islamic banking industry. The analysis results indicate that HHI has a negative effect on the stability of Islamic banks, as measured by the Z-score, supporting the competition-fragility hypothesis. The study concludes that while higher market concentration reduces stability, improved efficiency enhances resilience, suggesting future research should broaden data scope and include external and alternative stability factors.